Usage of EU Experience by Conclusion of Agreements Between the Subjects of the Russian Federation and Foreign States or Their Subjects Within the Scope of Economic, Scientific, Technical and Cultural Cooperation - S. Kashkin; S. Mikhailova; D. Korotkov (Informaciâ i Innovacii)
This article is devoted to the studying of rules of international agreements concluded between the subjects of the Russian Federation and foreign states or their subjects, and experience of European Union in using such kind of instruments. The article focuses on analyse of already existed agreements, necessity of harmonization and elaboration of framework agreement.